Methicillin resistance in Staphylococcus aureus strains isolated from food and wild animal carcasses in Italy. (December 2015) - Traversa, A.; Gariano, G.R.; Gallina, S.; Bianchi, D.M.; Orusa, R.; Domenis, L.; Cavallerio, P.; Fossati, L.; Serra, R.; Decastelli, L.
Abstract: Following the detection of methicillin-resistant Staphylococcus aureus (MRSA) ST398 in food-producing animals, both livestock and wildlife, and derived products, are considered potential sources of MRSA in humans. There is a paucity of data on MRSA in foods in Italy, and the data regarding wild animals are particularly scarce. A total of 2162 food samples collected during official monitoring activities in 2008 were analyzed for the detection of S. aureus . Also, samples from 1365 wild animals collected by the National Reference Center for Wild Animal Diseases in 2003–2009 were subjected to anatomopathological examination. S. aureus isolates were processed for phenotypic and molecular methicillin resistance determinations. S. aureus was found in 2.0% of wild animal carcasses and in 3.2% of wild boar lymph nodes: none showed methicillin resistance. The prevalence of S. aureus in food was 17.1%. Two MRSA strains, both from bulk tank milk (prevalence 0.77%) were isolated: the strains were resistant to tetracycline, had spa-type t899, and were negative for the Panton-Valentine leukocidin gene. The low prevalence of MRSA suggests that the risk of transmission to humans via food is limited. However, attention should be paid to the cattle food chain, which may be a potential route of transmission of LA-MRSA. Highlights: MRSA occurrence is low: the risk of transmission to humans via food is limited. 2 MRSA strains (0.77%), both spa -type t899, were isolated from bulk tank milk. MRSA t899, associated with ST398, was detected in bulk tank milk only in Italy. The cattle food chain may be a possible route of transmission of LA-MRSA to humans. Wild species had no MRSA but further studies on MRSA spreading are needed.